Probing the Impacts of MBKM Programs on Students’ Soft and Hard Skills - Rahma, Endah Anisa; Oktavinanda, Giovanni; Deping, Zou; Syahputri, Veni Nella (JL3T (Journal of Linguistics, Literature and Language Teaching), 2023)
Both soft skills and hard skills are vital to competence graduates’ competence in developing their potential according to their respective interests and skills. In line with these demands, this research aimed at exploring the impact of implementing MBKM on the improvement of soft skills and hard skills of Teuku Umar University students. The object studied are aspects of soft skills including communication skills, responsibility, honesty, fairness, ability to work together, adaptation, tolerance, respect for others, decision-making abilities and problem-solving abilities. Meanwhile, the components of the hard skills studied were foreign language skills, IT skills, reasoning skills, problem-solving skills, collaboration skills, understanding skills and creative thinking skills. The subjects of this study were Teuku Umar University students who had taken the MBKM program. The data were analyzed descriptively by using the percentage of each aspect of soft skills and hard skills. It was found that after joining the MBKM Program, first: students’ soft skills regarding the ability to communicate, responsibility, honest attitude, ability to use technology, to adapt, to be fair, to have cooperative and tolerant attitude, attitude, o respect others, and to make decisions increased up to 98%. Second, regarding the hard skills such as the ability to understand, the ability to reason, problem-solving skills, the ability to connect with other people, the ability to think creatively, the increased is reaching 96.6%. It is concluded that after joining the MBKM programs, the students’ softskills excel as expected.